Identification of pectolytic bacterial species isolated during plant bacteriosis in the Republic of Belarus - Chengyue, Shao; Gorovik, Yuri N.; Sidorova, Swetlana G.; Evtushenkov, Anatoli N. (Experimental Biology and Biotechnology, 2022)
During 2019 –2020, we selected 75 samples of potatoes, carrots, turnips, cabbage, onions, both in the field and from storage. Bacteria of the genus Pectobacterium were isolated from 60 samples. Strains of Bacillus pumilus, Bacillus sp. and Pseudomonas sp. were also isolated. The dominant species causing soft rot and black leg of potato were Pectobacterium carotovorum, P. parmentieri, P. atrosepticum and P. brasiliense. Bacterium P. carotovorum was isolated from other vegetable crops. In samples of carrots and potatoes, strains of bacteria of the genus Bacillus were often isolated from storage. For the first time in Belarus, we found the bacterium P. brasiliense on potato plants. The results obtained on the identification and spread of soft rot bacteria in Belarus will help plan the risks associated with infections caused by these pathogens.